Water insecurity a social dilemma - Abedin, Md. Anwarul; Habiba, Umma.; Shaw, Rajib (Bingley, U.K. : Emerald, 2013)
It has been estimated that globally, 1.2 billion people live with acute shortage of water. Water scarcity, particularly in south and south-east Asian countries, is well known. However, the social dilemmas and insecurities related to water issues are often less discussed. In the case of south and south-east Asia, the distribution of available water amongst various casts and creeds has been determined through several social hierarchies. Hence, water forms a critical socio-political issue, with a multi-faced dimension. This book critically analyses the associated social issues of increasing water scarcity in countries such as India. It documents the social impacts and predicament of water scarcity. The book will be of prime interest to researchers, policy makers and practitioners in the fields of development and environment, as well as water planners, and it will be a useful reference guide for future research in the field of water scarcity and risk management. Topics analysed include arsenic contamination, the impact of salinity on livelihood and mitigation, and drought resilience, adaptation and policy. The book concludes by providing lessons, challenges and future perspectives of water insecurity.
Defining water insecurity / Umma Habiba, Md. Anwarul Abedin, Rajib Shaw -- Global context of arsenic contamination in groundwater aquifers / Md. Anwarul Abedin, Rajib Shaw -- Community-level arsenic-mitigation practices in southwestern part of Bangladesh / Md. Anwarul Abedin, Rajib Shaw -- Social and institutional provisions for arsenic risk mitigation in West Bengal : achievements and challenges / Rajarshi DasGupta, Rajib Shaw -- Heavy metal pollution in the lower Gangetic mangrove ecosystem / Abhijit Mitra, Sufia Zaman, Subhra Bikash Bhattacharyya -- Salinity scenario in Mekong, Ganges, and Indus river deltas / Md. Anwarul Abedin, Umma Habiba, Rajib Shaw -- Salinity-induced livelihood stress in coastal region of Bangladesh / Umma Habiba ... [et al.] -- Rising water salinity : a threat to mangroves of Indian Sundarbans / Sufia Zaman ... [et al.] -- Water scarcity and migration : an Indian perspective / Mrittika Basu, Rajib Shaw -- Drought scenario in Bangladesh / Umma Habiba, Rajib Shaw -- Farmers' drought-adaptive practices in northwestern Bangladesh / Umma Habiba, Rajib Shaw -- Lessons, challenges, and future perspectives of water insecurity / Md. Anwarul Abedin, Umma Habiba, Rajib Shaw.
Print version record
Keywords: Science -- Environmental Science; Nature -- Environmental Conservation & Protection; Natural disasters; Management of land & natural resources; Water-supply.; Water consumption